Effectiveness of neuromuscular training based on the neuromuscular risk profile - Hewett, T. E.; Ford, K. R.; Xu, Y. Y.; Khoury, J.; Myer, G. D. (The American Journal of Sports Medicine, 2017)
Background: The effects of targeted neuromuscular training (TNMT) on movement biomechanics associated with the risk of anterior cruciate ligament (ACL) injuries are currently unknown. Purpose/Hypotheses: To determine the effectiveness of TNMT specifically designed to increase trunk control and hip strength. The hypotheses were that (1) TNMT would decrease biomechanical and neuromuscular factors related to an increased ACL injury risk and (2) TNMT would decrease these biomechanical and neuromuscular factors to a greater extent in athletes identified as being at a high risk for future ACL injuries. Study Design: Controlled laboratory study. Methods: Female athletes who participated in jumping, cutting, and pivoting sports underwent 3-dimensional biomechanical testing before the season and after completing TNMT. During testing, athletes performed 3 different types of tasks: (1) drop vertical jump, (2) single-leg drop, and (3) single-leg cross drop. Analysis of covariance was used to examine the treatment effects of TNMT designed to enhance core and hip strength on biomechanical and neuromuscular characteristics. Differences were also evaluated by risk profile. Differences were considered statistically significant at P < .05. Results: TNMT significantly increased hip external rotation moments and moment impulses, increased peak trunk flexion, and decreased peak trunk extension. Athletes with a high risk before the intervention (risk profile III) had a more significant treatment effect of TNMT than low-risk groups (risk profiles I and II). Conclusion: